2016
DOI: 10.1111/ijlh.12461
|View full text |Cite
|
Sign up to set email alerts
|

Flagging performance of the Sysmex XN2000 haematology analyser

Abstract: In conclusion, the combined use of WDF and WPC resulted in a reduction of approximately 25% of the number blood smears. As a result of the various techniques for light microscopy and haemocytometry, the adequacy of the XN flagging for abnormal and atypical lymphocytes cannot be established with certainty. To improve the quality of the reported results, it is recommended that laboratory technicians incorporate the haemocytometry results and the flagging information in the microscopic slide review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Despite the continuous improvement of the hematology analyzers, the flags are subject to ambiguities that require further examination. Several previous studies have evaluated the flagging performance of modern hematology instruments by comparing the data with the manual blood smear examination . Microscopic counting and characterization of blood cells have been considered as the reference method despite the fact that the method is cumbersome, time‐consuming, and also affected by inter‐observer differences.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the continuous improvement of the hematology analyzers, the flags are subject to ambiguities that require further examination. Several previous studies have evaluated the flagging performance of modern hematology instruments by comparing the data with the manual blood smear examination . Microscopic counting and characterization of blood cells have been considered as the reference method despite the fact that the method is cumbersome, time‐consuming, and also affected by inter‐observer differences.…”
Section: Introductionmentioning
confidence: 99%
“…However, an accurate analytical performance of the automated systems and also flagging abilities to identify the abnormal cells should be evaluated routinely. In recent years, studies have demonstrated a good correlation between automated leukocyte differentials and manual microscopy, and high accuracy, good precision, and linearity and also accurate flagging for abnormal cells were reported with different analyzers …”
Section: Introductionmentioning
confidence: 99%
“…In the XN series, detection of WBC abnormalities is based on a complex flagging algorithm guided by the information processing unit (IPU) software of the analyzer. The instrument can detect particular cell populations with an abnormal size, shape or position in the scattergrams 1,5,7,8,11,12 . Based on these findings, a Q ‐value is calculated.…”
Section: Methodsmentioning
confidence: 99%
“…In our laboratory, this XN series is composed of two XN‐10 and one XN‐20 modules, directly connected to a SP‐50–automated slidemaker‐stainer module and a DI‐60 digital cell imaging analyzer. Each XN module is equipped with a White Differentiation (WDF) channel, used for leukocyte differentiation and flagging for among which blast/abnormal lymphocytes, and the XN‐20 offers an additional White Progenitor Cell (WPC) channel that can differentiate between blasts and abnormal lymphocytes or can remove a false‐positive WDF flag in order to decrease manual microscopic review rate 1‐3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation